2016
DOI: 10.1016/j.healun.2016.01.717
|View full text |Cite
|
Sign up to set email alerts
|

ABO Blood Group and Bleeding Post-LVAD

Abstract: Purpose: Retrospective studies show that high dose aspirin (ASA) during Heart Mate (HM) II support is associated with more hemorrhagic events; however, limited prospective data exist on the impact of switching to reduced antiplatelet therapy. Methods: We implemented a clinical protocol to place all patients with HM II implantation (n= 26) from November 2014 to September 2015 on low dose aspirin (ASA) 81 mg daily. Concomitant anticoagulation with warfarin (target INR: 2-2.5) was maintained. Adverse events (AEs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…3 More recently, the relationship between ABO blood group and influence on COVID-19 susceptibility and outcomes has piqued the interest of the scientific community, with observational studies concluding that the odds for COVID-19 infection were significantly increased for blood group A and decreased for blood group O, 17,18 reinforcing the idea that ABO phenotypes may affect a multitude of physiologic processes including innate immunity. In the cardiac surgical setting, the relationship between blood group and bleeding has been studied in several different populations, with conflicting results-several smallscale studies of LVAD patients have failed to demonstrate a difference in bleeding rates between O and non-O groups, [19][20][21] whereas Welsby et al found that in CABG patients, O blood group did not have increased blood loss and instead required fewer RBC transfusions intraoperatively compared to their non-O peers. 5 On the other hand, Mazzeffi et al reviewed 111 patients consisting of both VV-ECMO and VA-ECMO and found that group O had a higher rate of massive transfusions (defined as ≥40 RBC units) compared to non-O blood groups and more RBC transfusions after controlling for confounders, although the proportion of patients with bleeding events did not differ with regard to blood type.…”
Section: Discussionmentioning
confidence: 99%
“…3 More recently, the relationship between ABO blood group and influence on COVID-19 susceptibility and outcomes has piqued the interest of the scientific community, with observational studies concluding that the odds for COVID-19 infection were significantly increased for blood group A and decreased for blood group O, 17,18 reinforcing the idea that ABO phenotypes may affect a multitude of physiologic processes including innate immunity. In the cardiac surgical setting, the relationship between blood group and bleeding has been studied in several different populations, with conflicting results-several smallscale studies of LVAD patients have failed to demonstrate a difference in bleeding rates between O and non-O groups, [19][20][21] whereas Welsby et al found that in CABG patients, O blood group did not have increased blood loss and instead required fewer RBC transfusions intraoperatively compared to their non-O peers. 5 On the other hand, Mazzeffi et al reviewed 111 patients consisting of both VV-ECMO and VA-ECMO and found that group O had a higher rate of massive transfusions (defined as ≥40 RBC units) compared to non-O blood groups and more RBC transfusions after controlling for confounders, although the proportion of patients with bleeding events did not differ with regard to blood type.…”
Section: Discussionmentioning
confidence: 99%